2021
DOI: 10.3390/ijerph18063022
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Critical Factors of Professionals’ BIM Adoption Behavior Based on the Theory of Planned Behavior

Abstract: In recent years, building information modeling (BIM) has been receiving growing interest from the construction industry of China. Nevertheless, although BIM has many foreseeable advantages, many studies claimed that these advantages have not been sufficiently achieved in practice at the current stage. In this circumstance, it is interesting to investigate what really drives the adoption of BIM. Based on Ajzen’s theory of planned behavior (TPB), a hypothetical model which involves nine latent variables is initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 109 publications
(128 reference statements)
0
10
1
Order By: Relevance
“…SN does not significantly influence BI, so there is no significant indirect influence on CR through “BI → CR”. This result is different from the research conclusions of Howard et al [ 13 ] and Wu et al [ 37 ], whose studies verified that individuals would be affected by surrounding people. The reason may be that their research is aimed at industry employees, and whether industry employees adopt BIM technology is more subject to the requirements of enterprises and industries [ 13 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…SN does not significantly influence BI, so there is no significant indirect influence on CR through “BI → CR”. This result is different from the research conclusions of Howard et al [ 13 ] and Wu et al [ 37 ], whose studies verified that individuals would be affected by surrounding people. The reason may be that their research is aimed at industry employees, and whether industry employees adopt BIM technology is more subject to the requirements of enterprises and industries [ 13 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Cronbach’s α coefficient is used to test the reliability of the questionnaire. It is generally believed that the questionnaire has good reliability when the Cronbach’s α coefficient reaches 0.8 [ 37 ]. The overall Cronbach’s α coefficient of the questionnaire was 0.959.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Success on growth of BIM usage by contractors witnessed in the developed world is not fully replicated in the developing world. While there has been success in improvement of BIM usage in a country like Chile that has had deliberate government interventions and mandates (Loyola and L opez, 2018), this cannot be said about China which Wu et al (2021) and Zhang et al (2020) have separately and independently concluded that by 2020, BIM usage among all actors was still low. In Kazakhstan, BIM usage is also low with cited barriers being low competency levels and lack of clear workflow processes (Aitbayeva and Hossain, 2020).…”
Section: Introductionmentioning
confidence: 99%